TANGGUNG GUGAT KASIR TERHADAP KERUGIAN AKIBAT KELALAIANNYA DI MATAHARI DEPARTEMENT STORE MALL LEMBUSWANA SAMARINDA - Khairunnisah Khairunnisah (LEGALITAS : Jurnal Ilmiah Ilmu Hukum, 2018)
In accordance with the 1945 Constitution, the Indonesian economy isstructured based on economic democracy, where business units or theeconomy are formed based on joint ventures and kinship with the networkmust be fostered a sense of shared responsibility for the business processso that interested parties get results that are worth the effort each one.Agreement is an event in which someone promises to another person or anevent in which someone promises to carry out in a matter in this eventarises a relationship between these two people which is called anengagement.According to article 1601 a Civil Code the employment agreement is anagreement whereby the one party namely the laborer binds himself to theother party (the employer) binds himself to employ one party (labor) bypaying a stipulated wage.The system that occurs at Mall Matahari Department Store where beforethe cashier's work is preceded by the existence of a work agreement in theform of a written agreement, the contents of the agreements are onlydetermined / made unilaterally, but the officer and employer agree. Sothat the officials felt like it or not had to implement the agreement made,because the agreement was binding. For an agreement between theemployer and the screen officer, the researcher uses the term workagreement which states that this agreement is about work, that is, theexistence of a work agreement arises from a party to work. What is clearin the agreement must be clear to both parties. So that one of them cannotget out of the agreement that has been agreed upon. And the agreementmust not harm one party or only benefit the other party (in this case theemployer / company).